A high-yield automated radiosynthesis of the alpha-7 nicotinic receptor radioligand [18F]NS10743. (January 2015) - Teodoro, Rodrigo; Wenzel, Barbara; Oh-Nishi, Arata; Fischer, Steffen; Peters, Dan; Suhara, Tetsuya; Deuther-Conrad, Winnie; Brust, Peter
Abstract: [ 18 F]NS10743, a promising and highly competitive α7 nAChR radioligand has been synthesized so far by microwave irradiation using a manual single-mode device followed by a palladium-catalyzed reduction of remaining nitro-precursor for HPLC separation purposes. For further preclinical and clinical use, regulated production of [ 18 F]NS10743 by fully automated radiosynthesis is a crucial requirement. Therefore, we chose a commercial synthesis module and developed the automated radiosynthesis of [ 18 F]NS10743. Besides evaluation of several radiosynthesis procedures, we performed an extensive HPLC study for quantitative separation of [ 18 F]NS10743 from the corresponding nitro precursor. After implementation of the optimized procedure on a TRACERlab TM FX F-N synthesis module, [ 18 F]NS10743 was obtained in high radiochemical purity (≥99%) with an overall radiochemical yield of 32.2±7% ( n =3). The specific activities at the end of the synthesis were 571±17 GBq/µmol ( n =3). Highlights: Development of a high-yield automated radiosynthesis of [ 18 F]NS10743. High radiochemical purity (>99%) and specific activities (571±17 GBq/µmol, EOS) were achieved. Successful HPLC separation of the [ 18 F]NS10743 from its respective nitro precursor was implemented.